2012
DOI: 10.1007/s00535-012-0671-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between metabolic syndrome and prevalence of gastroesophageal reflux disease in a health screening facility in Japan

Abstract: Metabolic syndrome is a reliable predictive factor for the prevalence of GERD, and medical therapy for metabolic syndrome may modify the risk of GERD occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 64 publications
8
55
0
Order By: Relevance
“…Lifestyle factors, such as eating foods with high components of fat or in large portions, alcohol intake, smoking, obesity, and metabolic syndrome, have also been reported to be related to a high prevalence of reflux esophagitis and GERD symptoms (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In addition, the factors shown to induce and/or worsen GERD have also been demonstrated to be associated with periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lifestyle factors, such as eating foods with high components of fat or in large portions, alcohol intake, smoking, obesity, and metabolic syndrome, have also been reported to be related to a high prevalence of reflux esophagitis and GERD symptoms (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In addition, the factors shown to induce and/or worsen GERD have also been demonstrated to be associated with periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…An increased gastroesophageal pressure gradient and hiatal hernia development have been reported to be induced by a high intra-abdominal pressure due to abdominal fat accumulation (3)(4)(5)(6)(7), while obesity and a high body mass index (BMI) have repeatedly been demonstrated to be associated with the high prevalence of reflux esophagitis and GERD symptoms (8)(9)(10)(11)(12)(13)(14)(15). In addition, metabolic syndrome, diagnosed by the presence of visceral fat accumulation, dyslipidemia, hypertension, and hyperglycemia, has been demonstrated to correlate with the occurrence of GERD (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GERD has been becoming more prevalent in Asian populations in recent decades, and although the disease is considered to be a common disorder in both Western and Asian populations, its increasing prevalence in Asia may be due to multiple factors, such as the Westernization of eating habits, decrease in the rate of Helicobacter pylori infection, increased gastric acid secretion and a larger elderly population, as well as other factors (2)(3)(4)(5)(6)(7)(8)(9). High intra-abdominal pressure caused by abdominal fat accumulation has been demonstrated to increase the gastroesophageal pressure gradient and incidence of gastroesophageal reflux, while obesity and a high body mass index (BMI) have repeatedly been reported to be correlated with a high prevalence of reflux esophagitis and symptoms of GERD (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). On the other hand, gender differences related to chronological changes in BMI and the prevalence of GERD have not been investigated in Japanese subjects, although a male predominance has been shown to be related to the frequency of reflux esophagitis and GERD (2-5, 8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…Several hypotheses have been proposed to explain this relationship, including i) increased intra-abdominal and intra-gastric pressure due to abdominal obesity, ii) the formation of an esophageal hiatal hernia, and iii) the intake of large amounts of foods and a high-fat diet, which increase the frequency of transient lower esophageal sphincter relaxation (TLESR). In contrast, the association between obesity and symptoms of GERD in Japanese patients remains unclear (5)(6)(7)(8)(9), although several studies in Japan have reported that visceral obesity was closely related to endoscopic reflux esophagitis, including Barrett's esophagus in patients with non-alcoholic fatty liver disease (NAFLD) (10), and metabolic syndrome was a risk factor for endoscopic reflux esophagitis (11).…”
Section: Introductionmentioning
confidence: 98%